On fiscal relations of the United Kingdom and Ireland, with special reference to the state purchase of land - Bailey, William F. (Statistical and Social Inquiry Society of Ireland, 1886)
A scheme was put forward some short time ago, which promised to effect a radical and sweeping change in the ownership of the land, without imposing any great hardship or additional burden on any class in the State. Mr. Giffen, the author of the scheme propounded, under the nom de plume "Economist" in the Statist early in the present year, claimed for his proposal that it would enable the imperial government to buy out every landlord in Ireland, giving him consols at par, equal in nominal amount to twenty years' purchase of the present judicial rents; to give the land free to the present occupiers, subject only to a rent-charge of one-half or two-thirds of the present judicial rents, payable to the new local authorities in Ireland, and to relieve the imperial exchequer of all payments now made out of it in connection with the local government of Ireland. Without in any way touching on the more purely political aspect of the question, my object is to consider the facts and figures on which Mr. Giffen's proposal is based, and submit his proposal to a more minute examination than has yet been given to it. To do this satisfactorily it will be necessary to analyze carefully the present burden of local and imperial taxation in Ireland, and define the existing and forecast the future financial relations between the exchequers of Great Britain and Ireland. Before dealing with the proposed future financial relations between the two countries, it will be necessary to state carefully the present position of affairs, so that we may thoroughly understand the circumstances with which we have to deal, and the existing interests which we must take into account.
Read Tuesday, 13th April, 1886.
Keywords: Land purchase; Fiscal relations; 314.15